2005
DOI: 10.1038/sj.bmt.1704970
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells rescue CD34+ cells from radiation-induced apoptosis and sustain hematopoietic reconstitution after coculture and cografting in lethally irradiated baboons: is autologous stem cell therapy in nuclear accident settings hype or reality?

Abstract: Summary:Autologous stem cell therapy (ACT) has been proposed to prevent irradiated victims from bone marrow (BM) aplasia by grafting hematopoietic stem and progenitor cells (HSPCs) collected early after damage, provided that a functional graft of sufficient size could be produced ex vivo. To address this issue, we set up a baboon model of cell therapy in which autologous peripheral blood HSPCs collected before lethal total body irradiation were irradiated in vitro (2.5 Gy, D 0 1 Gy) to mimic the cell damage, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…We found that HKMT protected bone marrow structure and restored the number of nucleated cells. CD34+ hemopoietic stem cells (HSCs) were the source of almost all the blood cells and immunocytes [27]. Our data also showed that HKMT increased the number of HSCs in bone marrow after irradiation.…”
Section: Hkmt Inhibited Radiation Injuries On Testis Tissuessupporting
confidence: 69%
“…We found that HKMT protected bone marrow structure and restored the number of nucleated cells. CD34+ hemopoietic stem cells (HSCs) were the source of almost all the blood cells and immunocytes [27]. Our data also showed that HKMT increased the number of HSCs in bone marrow after irradiation.…”
Section: Hkmt Inhibited Radiation Injuries On Testis Tissuessupporting
confidence: 69%
“…Further analyses in a primate model found detectable levels of allogeneic GFP-labeled MSCs in irradiated bone marrow samples up to 80 days after infusion, correlating with the repair of radiation damage and increased survival times [42]. Co-transplantation of MSCs with hematopoietic stem cells resulted in a stable multi-lineage engraftment and hematopoietic recovery [37,43]. It has been suggested that transplantation of MSCs alone without the addition of hematopoietic stem cells could also recover irradiated bone marrow and even result in improved survival [38,44].…”
Section: Bone Marrowmentioning
confidence: 96%
“…Moreover, MSCs therapy resulted in improved recovery of the hematopoietic system through decreased apoptosis and radiation induced oxidative stress [167,168].…”
Section: Hematopoietic System Homeostasis Radiation Injurymentioning
confidence: 99%